PENGARUH SUBTITUSI EKSTRAK RUMPUT LAUT COKLAT TERHADAP KUALITAS BAKSO AYAM AFKIR - Oktavia, Nora; Faridah, Anni; Syarif, Wirnelis (Journal of Home Economics and Tourism, 2017)
The research was distributed by the utilization of the Brown seaweed in food processing have not been there. This research aims to analyze the influence of Brown seaweed extract substitutions as much as 5 ml, 15 ml 10ml, and to the quality of the chicken Meatball afkir in terms of shape, colour, aroma, texture and taste. This type of research is purely experiment (true experimental) using random cluster design method. The type of the data being used is the primary data sourced from 30 panelists by filling the organoleptic format towards the sample. The data already acquired and then tabulated in the form of tables and done the analysis Variant (ANAVA). If different real continued with further test Duncan. Results of the study showed there was significant influence between the 5 ml, 15 ml 10ml, and substitution of Brown seaweed extract against chicken meatballs afkir namely quality on the quality of color and texture. Quality round shape with a diameter of 2 cm, the shape of a uniform, distinctive scent of chicken meatballs, fibrous texture is smooth and savory flavor has no effect on the quality of the chicken Meatball afkir. The results of the quality of the chicken Meatball afkir best is 15 ml.Keywords: brown seaweed, chicken Meatball afkir, The Quality Of Organoleptik